148k views
0 votes
What is the factored form of 25b^2 -60b+36

User TheIV
by
5.4k points

2 Answers

6 votes

Answer:

(5b - 6)(5b - 6)

Step-by-step explanation;

25b^2 - 60b + 36

=> (5b)^2 - 2 × 5b × 6 + (6)^2 [Using (a + b)^2 = a^2 + b^2 + 2ab]

=> (5b - 6)^2

=> (5b - 6)(5b - 6)

User Fooman
by
6.4k points
5 votes

Answer:

(5b-6)^2

Explanation:

by using formula

(a-b)^2 = (a)^2 - 2(a)(b) + (b)^2

by putting values in the above formula

(5b)^2 - 2(5b)(6) + (6)

(5b-6)^2 answer

User Alexander Shostak
by
5.9k points